Operative internal fixation of isolated femoral diaphyseal fractures – is interlocking nail the best option? - ZF, Zairul-Nizam (IIUM Medical Journal Malaysia, 2008)
Femoral fractures are one of the commonest fractures encountered in orthopaedic practice. Over the years, treatment of this injury has evolved tremendously. The initial non-operative methods of reduction and stabilization have largely been replaced by operative fixation. There are currently three basic modes of internal fixation of femoral diaphyseal fractures in the adult age group: plate and screws, intramedullary Kuntscher nailing, and interlocking nailing. The objective of this study is to determine whether the socalled more ‘technologically advanced’ interlocking nailing results in better outcome compared to the more ‘traditional’ plate and screws, and Kuntscher nailing. It is found that, in terms of time to union and final function after an average of just under 2 years post-operative period, the group of patients who had interlocking nailing fared poorer. A review of relevant literature will then be presented.